Wettability of tungsten carbide by liquid binders in WC–Co cemented carbides: Is it complete for all carbon contents?. (January 2017) - Konyashin, I.; Zaitsev, A.A.; Sidorenko, D.; Levashov, E.A.; Ries, B.; Konischev, S.N.; Sorokin, M.; Mazilkin, A.A.; Herrmann, M.; Kaiser, A.
Abstract: The wettability of tungsten carbide by liquid binders with various carbon contents and infiltration of WC–WC grain boundaries in cemented carbide by such binders were examined. The wettability of tungsten carbide by the liquid Co-based binder is complete at low carbon contents and becomes incomplete when increasing the carbon content. The wettability of WC by the Co-based binder alloy saturated with carbon is relatively poor with a wetting angle of about 15°. The well-known phenomenon of Co migration from carbide regions with high carbon contents into regions with low carbon contents is presumably caused mainly by the variance in capillary forces related to the different wettability rates of WC by liquid binders with various carbon contents. The Co-based binders with various carbon contents are found to have different behaviors with respect to infiltrating WC–WC grain boundaries in cemented carbides during sintering. WC–WC interfaces in a cemented carbide sample with a high carbon content do not comprise nm-thick Co interlayers. In contrast to that, the majority of the WC–WC interfaces in a cemented carbide sample with a low carbon content comprise continuous Co interlayers of the order of at least several nanometers in thickness. Highlights: Wettability of WC by liquid binders with various carbon contents was examined. Wettability of WC by a liquid Co-based binder is complete at low carbon content. Wettability of WC by a liquid binder becomes incomplete when increasing carbon content. WC–WC interfaces in high-carbon cemented carbide do not comprise nm-thick Co interlayers. WC–WC interfaces in low-carbon cemented carbide comprise nm-thick Co interlayers.